1987
DOI: 10.1111/j.1439-0442.1987.tb00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Adaptation to Repeated Emotional Stress Evoked by Isolation of Sheep from the Flock*

Abstract: The aim of this study was to examine whether sheep can adapt to emotional stress evoked by individual isolation from the flock. The experiments were performed on 12 sheep divided into 2 groups; the control (kept in the sheepfold) and the experimental group in which sheep were isolated 3 times for 5 h at 3-day intervals, The plasma concentration of cortisol and glucose served as indicators of stress. It was found that during 3 consecutive isolations the cortisol level rose on average 3-fold above the initial va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…Moreover, isolation of goats from their social group causes a greater elevation of cortisol concentrations if the animals are not able to maintain visual contact with other animals [17]. Several authors have also shown no habituation of sheep to isolation on the basis of cortisol concentrations [26,31]. Therefore, in our experiment, the goats might have been able to adapt to transportation but not to isolation.…”
Section: Control (N = 23) Trans (N = 21) Probabilitymentioning
confidence: 71%
“…Moreover, isolation of goats from their social group causes a greater elevation of cortisol concentrations if the animals are not able to maintain visual contact with other animals [17]. Several authors have also shown no habituation of sheep to isolation on the basis of cortisol concentrations [26,31]. Therefore, in our experiment, the goats might have been able to adapt to transportation but not to isolation.…”
Section: Control (N = 23) Trans (N = 21) Probabilitymentioning
confidence: 71%
“…The increased level of cortisol might be attributed to the stimulation of hypophysis pituitary axis (HPA) by restraining and handling of animals for epidural injection and recording of parameters. Restraining, handling and even isolation has been reported to cause hypercortisolaemia in lambs (Minto and Blecha, 1990) and ewes (Niezoda et al., 1987). In groups A and C, the nearly equal amount of increase in cortisol concentration indicates that ketamine did not enhance stress, as induced by xylazine.…”
Section: Discussionmentioning
confidence: 99%
“…By applying these results to a commercial preslaughter situation, evidently the longer the animals remain in isolation, the greater will be the emotional stress they experience. Small ruminants do not readily adapt to social isolation, as repeated application of isolation stress evokes a greater increase in circulating cortisol concentrations (Niezgoda et al, 1987). Grandin (1998) emphasized that animals should not be left in a restrainer or stunning pen at slaughter facilities for prolonged durations, such as during lunch or coffee breaks.…”
Section: Discussionmentioning
confidence: 99%